y = mx + b; Slope - intercept form of a linear equation; where m is the slope, or rate of change, and b is the y - intercept.
c) 3y + 2 = 2y - 5x
3y - 2y = -5x - 2
y = - 5x - 2 (pattern of change is -5 and y - intercept is -2).
d) 2(y - 3) = 2x - 6
2y - 6 = 2x - 6
2y = 2x - 6 + 6
2y = 2x
y = x (pattern of change is 1 and y - intercept is 0)
e) 5 - 3(x + 1) = 2y - 3x + 2
5 - 3x - 3 = 2y - 3x + 2
-2y = -3x + 3x + 2 + 3 - 5
-2y = 0
y = 0 (pattern of change is 0 and y - intercept is 0)
f) x - (y + 2) = 2(2x + 1)
x - y - 2 = 4x + 2
-y = 4x - x + 2 + 2
-y = 3x + 4
y = -3x - 4 (pattern of change is -3 and y - intercept is -4)